VOX Spain: The Organisational Challenges of a New Radical Right Party - Barrio, Astrid (2021)
This article examines the organisation of VOX, a new radical right party in Spain. It shows that the party has taken early and uneven steps to build a mass organisation and initially opted for open membership recruitment with participatory organisational elements. Also, the party’s rapid growth and quick entrance into political institutions at different state levels led the party leadership to establish more centralised control and limit members’ prerogatives, though recruitment continued. Centralisation in part responds to organisational needs given the party’s quickly acquired political relevance, but also to the desire of the central party leadership to forestall the articulation of territorial interests, or prevent them from escaping their control. Today, VOX exhibits elements of mass party organisation and highly centralised decision-making in the hands of national party leaders.